El aprendizaje activo como estrategia didáctica para el aprendizaje de Química Inorgánica, con los estudiantes de tercer semestre de la carrera de la Pedagogía de las Ciencias Experimentales Química y Biología, periodo octubre 2020-marzo 2021. - Cali Armijo, Fabián Edelberto (2021)
Promoting active learning in students is necessary in view of the new educational reality at the higher level. The Inorganic Chemistry subject, taught in the classroom through the scarce use of active strategies generates rote learning, demotivation, lack of interest, passive attitudes and behaviors. Therefore, the objective was: "To propose active learning as a didactic strategy in the learning of Inorganic Chemistry". The research methodology based on a non-experimental, bibliographic and field design; a methodological guide developed and socialized on the use of gamification for active learning of Inorganic Chemistry in topics on the stoichiometry of the composition and classification of chemical reactions; the research had a descriptive level. To collect the data, the survey applied as a technique and the questionnaire with 10 questions as an instrument; there was a population of 38 students of the third semester in the October 2020-March 2021 period, of the Pedagogy of Experimental Sciences, Chemistry and Biology. Based on the results, it could be evidenced that all students considered that the active strategy favors active learning of Inorganic Chemistry. It concluded that active learning implies the development of an active and participatory attitude in students, thus strengthening capacities, skills and competencies for meaningful learning of the subject. It suggested to enhance the active role of students through strategies that inculcate commitment to the activities and motivate the construction of learning.